COMPOSITIONAL SIMULATION OF SOUR GAS RE-INJECTION INTO CARBONATE RESERVOIRS - Suleimen, Mukhabbat (Nazarbayev University School of Mining and Geosciences, 2022)
One of the major obstacles considering ecology is sour gas, which accompanies natural gas in almost half of all producing reserves in the world. The major oilfields in North Caspian Sea Region all produce high concentration of sour gas. However, only during the last decades has sour gas been used for enhanced oil recovery (EOR) for twin advantages, both economically and environmentally. Sour oil and gas, with high acidic gas content such as hydrogen sulfide and carbon dioxide, have high toxicity and cause corrosion of equipment. Overcoming most of these challenges in carbonate reservoirs with high H2S content would facilitate oilfields to keep the supply high enough to meet the high oil and gas demand. This work first conducted a literature review about the application of H2S flooding in oil reservoirs. Then CMG compositional simulator was used to investigate the feasibility of sour gas injection into carbonate reservoir for EOR. Injection of CH4/H2S and CO2/H2S gas mixtures into reservoir sector models were simulated for assessing oil recovery potential. The results of modeling four different reservoir models, including 2D homogeneous, 2D heterogeneous, 3D homogeneous, and 3D heterogeneous models, showed high concentration sour gas injection is superior as compared to low concentration gas mixtures. Sour gas injection with high H2S content achieved higher oil production rate than other low content cases, this can be attributed to the increase in displacing fluid viscosities toward lower mobility ratios during the injection and easier miscibility of H2S with crude oil.
Keywords: enhanced oil recovery; EOR; CMG; North Caspian Sea Region; International Energy Agency; Type of access: Gated Access; IEA; carbonate reservoirs; sour gas re-injection